Uncoordinated psychosocial network compromising the integrality of care - Maria de Fátima Alves Aguiar Carvalho; Edméia de Almeida Cardoso Coelho; Jeane Freitas de Oliveira; Rosália Teixeira de Araújo; Andiara Rodrigues Barros (SciELO, 2018)
ABSTRACT Objective To discuss the lack of coordination in the Psychosocial Care Network from the conception of professionals of a Psychosocial Care Center for Alcohol and Drugs (Portuguese acronym: CAPSad). Method Qualitative study conducted with professionals from a CAPSad unit. The empirical material was produced through two reflection workshops focused on care experiences, and analysis using the discourse analysis technique. The category of analysis was integrality. Results Nine professionals participated in the study. All of them reported being part of a disarticulated service network, in disagreement with principles of the national mental health policy, which directly affects the resolution of care provided in the unit. Conclusion The operating logic in the Psychosocial Care Network tends to reduce the care of drug users to the CAPSad assistance, hence compromising the integrality of care.